The Impact of Work Discipline and Work Ethic on the Teacher Performance of Sultan Agung Pematangsiantar Private Middle School Teachers T.A. 2018/2019 - Acai Sudirman; Darwin Lie; Sherly Sherly; Edy Dharma (Sekolah Tinggi Manajemen IPMI, 2020)
This study aims to examine the effect of work discipline and work ethic on the performance of Sultan Agung Private Middle School teachers. The number of samples in this study were 31 teachers obtained by the census method. The instrument used in this study was a questionnaire that was distributed directly to the teacher as a respondent. Testing research instruments using validity and reliability tests. Data analysis used multiple linear regression, correlation, coefficient of demertination, simultaneous and partial test. The results of the research and hypothesis testing show that work discipline variables and the ethic of apes have a positive and significant effect on teacher performance. The empirical findings indicate that in order to improve work discipline at Sultan Agung Pematangsiantar Private Middle School there needs to be a transparent system in recruiting permanent teachers who only teach at Sultan Agung Pematangsiantar Private Middle School so that the teacher focuses on his/her work. Then to improve the work ethic of Sultan Agung Pematangsiantar Private Middle School teachers, the principal as the leader should be able to provide personal and organizational motivation so that every teacher who works can maintain a balance of work ethic competently. Furthermore, to improve performance, every teacher should have the characteristics of self-enhancing potential so that the consistency of teacher professionalism can develop.